Biomechanical Assessment of Locking Plate Fixation of Comminuted Proximal Olecranon Fractures. Issue 11 (November 2018) - Fantry, Amanda; Sobel, Andrew; Capito, Nicholas; Hodax, Jonathan D.; Pidgeon, Tyler; Koruprolu, Sarath; Rich, Ryan; Fava, Joseph L.; Green, Andrew; Paxton, Scott
Abstract : Objectives: To determine if mean ultimate strength or failure mechanism differed between comminuted olecranon fractures created at the proximal 25% or 50% of the trochlear notch and fixed with precontoured posterior locking plates (PLPs). Methods: Comminuted osteotomies were created in 10 matched pairs of cadaveric upper extremities at either the proximal 25% or 50% of the trochlear notch after quantitative computed tomography scans were performed to evaluate bone mineral density. Variable-angle olecranon PLPs were fixed to the specimens. The triceps tendon of each specimen was loaded cyclically and then to failure. Comparison of mean force at failure (displacement >2 mm) was performed using the 2-tailed t test. Results: There were no significant differences in specimen bone mineral density within matched pairs. Nineteen specimens failed by olecranon bisection fracture in the sagittal plane. Specimens in the 25% osteotomy group failed at lower ultimate forces of 808 N (SD ± 474 N) versus 1058 N (SD ± 480 N) in the 50% osteotomy group ( P = 0.044). Conclusions: The ultimate strength of comminuted olecranon fracture fixation with a PLP decreases significantly if the fracture is proximal to the midpoint of the trochlear notch. Fractures proximal to the midpoint of the trochlear notch may benefit from supplemental fixation or suture augmentation to prevent failure, particularly at force ranges higher than those experienced during active elbow range of motion.